2012
DOI: 10.1016/j.neuron.2012.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Hearing in the VGLUT3 Knockout Mouse Using Virally Mediated Gene Therapy

Abstract: Summary Mice lacking the vesicular glutamate transporter-3 (VGLUT3) are congenitally deaf due to loss of glutamate release at the inner hair cell afferent synapse. Cochlear delivery of VGLUT3 using adeno-associated virus-1 (AAV1) leads to transgene expression in only inner hair cells (IHC), despite broader viral uptake. Within two weeks of AAV1-VGLUT3 delivery, acoustic brainstem response (ABR) thresholds normalize, along with partial rescue of the startle response. Lastly, we demonstrate partial reversal of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
383
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 334 publications
(399 citation statements)
references
References 39 publications
13
383
1
2
Order By: Relevance
“…Prior studies had shown some transduction of IHCs with conventional AAVs, but little transduction of OHCs. 12,23 We found that exo-AAV1 efficiently transduces IHCs and transduces OHCs much more efficiently than does conventional AAV1. AAV1 was our standard of comparison because it has been used in prior studies of hearing gene therapy.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Prior studies had shown some transduction of IHCs with conventional AAVs, but little transduction of OHCs. 12,23 We found that exo-AAV1 efficiently transduces IHCs and transduces OHCs much more efficiently than does conventional AAV1. AAV1 was our standard of comparison because it has been used in prior studies of hearing gene therapy.…”
Section: Discussionmentioning
confidence: 89%
“…AAV1 was our standard of comparison because it has been used in prior studies of hearing gene therapy. 12,13 In those studies, it was shown to only transduce inner hair cells relatively efficiently. Interestingly, we found that exo-AAV9-GFP was extremely efficient at transduction of cochlear explant cultures, although, in vivo, this serotype performed similarly to exo-AAV1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations